2023
DOI: 10.1111/jeu.12976
|View full text |Cite
|
Sign up to set email alerts
|

The photic‐aphotic divide is a strong ecological and evolutionary force determining the distribution of ciliates (Alveolata, Ciliophora) in the ocean

Abstract: The bulk of knowledge on marine ciliates is from shallow and/or sunlit waters. We studied ciliate diversity and distribution across epi‐ and mesopelagic oceanic waters, using DNA metabarcoding and phylogeny‐based metrics. We analyzed sequences of the 18S rRNA gene (V4 region) from 369 samples collected at 12 depths (0–1000 m) at the Bermuda Atlantic Time‐series Study site of the Sargasso Sea (North Atlantic) monthly for 3 years. The comprehensive depth and temporal resolutions analyzed led to three main findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…For example, Syndiniales composition varied by season (PERMANOVA R 2 = 0.2 and 0.11; P -value < 0.001) at depths in the photic zone (e.g., 1 and 120 m), while seasonal changes were not significant at deeper depths (e.g., 600 and 1000 m). Other 18S rRNA gene metabarcoding studies at this site [ 33 , 34 ] and in the North Pacific [ 17 ] have noted significant variability in protist composition and diversity with depth compared with weaker seasonal signals. Seasonality in the Sargasso Sea is characterized by deep convective mixing (~150–300 m) between January and March and stratification of the water column (mixed layer depth < 20 m) as early as May [ 32 ], driving seasonal patterns in phytoplankton, heterotrophic bacteria, and viruses [ 39–41 ].…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…For example, Syndiniales composition varied by season (PERMANOVA R 2 = 0.2 and 0.11; P -value < 0.001) at depths in the photic zone (e.g., 1 and 120 m), while seasonal changes were not significant at deeper depths (e.g., 600 and 1000 m). Other 18S rRNA gene metabarcoding studies at this site [ 33 , 34 ] and in the North Pacific [ 17 ] have noted significant variability in protist composition and diversity with depth compared with weaker seasonal signals. Seasonality in the Sargasso Sea is characterized by deep convective mixing (~150–300 m) between January and March and stratification of the water column (mixed layer depth < 20 m) as early as May [ 32 ], driving seasonal patterns in phytoplankton, heterotrophic bacteria, and viruses [ 39–41 ].…”
Section: Resultsmentioning
confidence: 77%
“…Recent 18S rRNA gene metabarcoding work at BATS revealed a high relative abundance of Syndiniales (~40%) throughout the water column [ 33 ] and their presence in sediment traps [ 20 ]. Moreover, several studies at BATS [ 33 , 34 ], and in other oligotrophic systems [ 17 ], have observed significant shifts in protist diversity and composition with depth, with communities varying less over seasonal cycles. We performed covariance network analysis of a 4-year (2016–19) 18S rRNA gene metabarcoding dataset [ 33 ], constructing networks for each of 12 discrete depths (1–1000 m).…”
Section: Introductionmentioning
confidence: 99%
“…Surface water in the ECS is mainly mixed by the CDW, KSW, and TCWW, while the deeper layer is influenced by KSSW, Shelf Mixing Water (SMW), and TCWW by the Optimum Multiparameter analysis (Zhou et al, 2018). Ciliate community composition and diversity reported differ markedly with depth (Countway et al, 2010;Grattepanche et al, 2016a, b;Santoferrara et al, 2023;Tucker et al, 2017;Zhao et al, 2017;Wang et al, 2021a), water masses (Sun et al, 2020;Yang et al, 2020;Gu et al, 2021), and geographical position (inshore/offshore) (Grattepanche et al, 2015;Santoferrara et al, 2016;Grattepanche et al, 2016b). While Yang et al (2020) indicated that planktonic ciliates were potentially reliable indicators of water masses in the ECS, this was not universally consistent, possibly due to methodological differences in definitions of water masses or ciliate analysis approaches (Zhang et al, 2015).…”
Section: Hydrographic Conditions Shape Small-sized Ciliate Community ...mentioning
confidence: 99%